Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

tanA=sinA/cosA

cotA=cosA/sinA

therefore

**tanA=1/cotA**

using the identity cosec^2A-cot^2A=1

we get cosec^2A=1+cot^2a

1/sin^2A=1+cot^2A

sin^2A=1/1+cot^2A

**sinA=(1/1+cot^2A)^1/2**

using identity sec^2A-tan^2A=1

we get

sec^2A=1+tan^2A

sec^2A=1+1/cot^2A

sec^2A=cot^2A+1/cot^2A

**secA=(cot^2A+1/cot^2A)^1/2**